Novel space time frequency diversity for multiple input multiple ouput-orthogonal frequency division multiplexing (MIMO-OFDM) by using equalizer / Mohammad Yazzed Akhmat - Akhmat, Mohammad Yazzed (2007)
This project proposes novel space-time-frequency block codes (STFBC) for multiantenna orthogonal frequency-division multiplexing (OFDM) transmissions over frequency selective fading channels (Multipath Rician and Multipath Rayleigh) by using QPSK modulation and a receiver equalizer. The resulting codes are to be capable of achieving maximum diversity and coding gains, while affording low-complexity decoding. The performance merits of this design is confirmed by corroborating simulations and compared with existing alternatives. In the Space Time Frequency (STF) coding schemes, assuming symbols Si, S2, S3 and S4 are transmitted a codeword constituted as Ci, C2, C3 and C4 as symbol sets, transmitted at the same time slot but over two different OFDM sub-channel frequency carriers, fcl and fc2.